The last sunrise [large type] - Todd, Anna (Thorndike Press large print dynamic drama., 2025)
Between chronic health issues and an over-protective mother, twenty-two-year-old Oriah Pera feels like she's waiting for her life to begin. But when her mother's job takes them to Majorca, Ry knows this summer could be the start of her very own coming-of-age story. She heads off to the beach and meets a charming Spaniard. Julian makes Ry feel even more naive and inexperienced than she normally does, but she can't tamp down her attraction. As the summer continues, Julian pulls Ry out of her shell and into the adventures she's always craved. But with her return to America looming, Ry must decide if she's brave enough to finally follow her heart and live for herself.--